Studi Empiris Tentang Pengaruh Volume Perdagangan dan Return terhadap Bid-Ask Spread Saham Industri Rokok di Bursa Efek Jakarta Dengan Model Koreksi Kesalahan - Abdul Halim; Nasuhi Hidayat (The Indonesian Journal of Accounting Research, 2013)
In US Capital Market, the empirical evident showed that the effect of inventory holding cost of stock on bid-ask spread was positive.  This paper attempts to confirm the effect in Indonesian Capital Market.  The confirmation is performed by using the error correction model (ECM).  The case in cigarette industry is used in this paper.  There are three companies in this industry including PT BAT, PT H.M. Sampoerna, and PT Gudang Garam.The daily time series data for the year 1996, 1997, and 1998 are used to be analyzed.  It was found that the ECM estimation gave the evident that the transaction volume and/or return negatively effects on bid-ask spread both in term of absolute and relative in cigarette industry.  It means that the inventory holding cost of stock on bid-ask spread would be positive.  Accordingly, the finding is consistent and confirmed.